SOLID WASTE ANALYSIS AND PROCESSING POTENTIAL IN THE TOURISM SECTOR: CASE STUDY IN NUSA DUA, SOUTH KUTA, BALI - I Made Wahyu Widyarsana; Made Ayu Priyanka; Lahur Akbar Devianto (Universitas Trisakti, 2022)
Aims: The study of waste generation and composition in 6 types of tourism facility in Nusa Dua is carried out to analyze the waste processing potential and determine a proper waste management needed for tourism areas. Methodology and results: The primary data collection methods including field observations for existing waste separation, sampling of waste generation and composition at source, interviews with the facility’s management and characteristics of certain types of waste. Meanwhile, secondary data of waste generation and composition for hotels and the mall is acquired from waste collection services in Nusa Dua and previous studies for typical facilities. Nusa Dua produces around 11 tons of waste per day with hotels being the highest contributor of waste compared to other tourism facilities. The waste produced in Nusa Dua comprises around 70% of organic waste including food and yard waste and the remaining 30% includes paper, plastic, glass, metal, and other waste. Conclusion, significance and impact study: Aside from maximizing waste processing, Nusa Dua should execute campaigns to support the government’s regulation regarding the ban on styrofoam products, plastic bags, and plastic straws which gradually will reduce the amount of non-recyclable waste produced by the area.